2002
DOI: 10.1074/jbc.m108986200
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Helix-Loop-Helix Factor Id2 to Regulation of Vascular Smooth Muscle Cell Proliferation

Abstract: Smooth muscle cell (SMC) proliferation plays a key role in vascular proliferative disorders. The molecular mechanisms that control cell cycle entry of SMCs in response to vascular injury are not well understood. Id2 (inhibitor of DNA binding) is a member of the helix-loophelix (HLH) family of transcription regulators that are known to promote cell cycle progression. Thus, we investigated the role of Id2 in SMC growth and cell cycle regulation. The results demonstrated that overexpression of Id2 resulted in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
58
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 16 publications
10
58
1
Order By: Relevance
“…In support of this notion, there is a Interference of ID1 with either the pRb or the p53 tumor suppressor pathway is unlikely to contribute to the observed cellular phenotype, since ID1 was able to induce centrosome abnormalities in SaOS-2 human osteosarcoma cells that contain mutated p53 and pRb (Lauricella et al, 2001). ID-proteins have been shown do inhibit the expression of the CDK-inhibitory proteins p16 INK4A , p21 Waf1/Cip1 , and p27 Kip1 (Lasorella et al, 1996;Prabhu et al, 1997;Pagliuca et al, 2000;Alani et al, 2001;Ohtani et al, 2001;Matsumura et al, 2002;Mueller et al, 2002;Tang et al, 2002). Since all IDproteins were able to inhibit expression of a p21 Waf1/Cip1 reporter construct, we consider it unlikely that ID1 induces centrosome abnormalities through inhibition of p21 Waf1/Cip1 even though repression of p21 Waf1/Cip1 using antisense constructs in human hematopoietic cells results in centrosome abnormalities (Mantel et al, 1999).…”
Section: Discussionmentioning
confidence: 67%
“…In support of this notion, there is a Interference of ID1 with either the pRb or the p53 tumor suppressor pathway is unlikely to contribute to the observed cellular phenotype, since ID1 was able to induce centrosome abnormalities in SaOS-2 human osteosarcoma cells that contain mutated p53 and pRb (Lauricella et al, 2001). ID-proteins have been shown do inhibit the expression of the CDK-inhibitory proteins p16 INK4A , p21 Waf1/Cip1 , and p27 Kip1 (Lasorella et al, 1996;Prabhu et al, 1997;Pagliuca et al, 2000;Alani et al, 2001;Ohtani et al, 2001;Matsumura et al, 2002;Mueller et al, 2002;Tang et al, 2002). Since all IDproteins were able to inhibit expression of a p21 Waf1/Cip1 reporter construct, we consider it unlikely that ID1 induces centrosome abnormalities through inhibition of p21 Waf1/Cip1 even though repression of p21 Waf1/Cip1 using antisense constructs in human hematopoietic cells results in centrosome abnormalities (Mantel et al, 1999).…”
Section: Discussionmentioning
confidence: 67%
“…Overexpression of Id proteins in embryonic-derived fibroblasts facilitates cell cycle S-phase under serum-deprived conditions [34], where Id-1 has been reported to induce the proliferation of cochlear sensory epithelial cells via the NF-kappaB/cyclin D1 pathway [35]. Furthermore, various cancer cell lines appear to require Id-1 and Id-2 expression for their growth, survival, and metastasis via regulation of p53 and PI3K/Akt/NF-kappaB signaling pathways in a similar fashion to that described for Twist-1 and Dermo-1 [36][37][38][39][40]. More recently, Id-1 has been shown to mediate long-term repopulating hematopoietic stem cell maintenance and inhibit myeloid differentiation [41,42].…”
Section: Discussionmentioning
confidence: 92%
“…Evidence available suggests that Id proteins are localized in the cytoplasm rather than the nucleus in a variety of cells such as hemopoietic [20], neural [21], muscle [22], and renal cells [23]. These findings therefore suggest that translocation between the nucleus and the cytoplasm (nucleocytoplasmic shuttling) may be involved in the functional regulation of Id proteins.…”
Section: Discussionmentioning
confidence: 96%
“…Evidence available shows that Cyclin A-and Cyclin E-dependent CDK2 phosphorylation of Id2 and Id3 proteins at a conserved serine residue at position 5 regulates the ability of these proteins to antagonize bHLH-dependent gene expression [12]. It has also been shown that phospho-ablated Id2 Ala5 mutant where serine at position 5 is mutated to an Alanine is growth inhibitory in fibroblasts, smooth muscle cells and osteosarcoma cell lines [12,22]. Literature available also suggest that Id2-induced apoptosis is promoted through a mechanism different from what is used by other Id proteins.…”
Section: Discussionmentioning
confidence: 99%